Expectations of prospective orthodontic patients regarding post-orthodontic retention - Mahida, Hafsa Khalid; Sarwat Memon; Memon, Jaweria (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the awareness among patients of prospective orthodontics about post-orthodontic retention. Method: The cross-sectional study was conducted from May 2022 to May 2023 at the Department of Orthodontics, Ziauddin University, Karachi, and comprised patients of either gender enrolled for their first appointment at the outpatient clinic. Each patient received a validated questionnaire which explored their understanding, attitudes and expectations regarding the importance of retention after orthodontic treatment. Data was analysed using SPSS 25. Results: Of the 206 questionnaires distributed, 203(98.5%) were returned duly filled. The overall mean age of the sample was 20.25±5.24 years (range: 8-48 years). There were 131(64.5%) females with mean age 12±3.2 years, and 72(35.5%) males with mean age 16±2.1 years. Majority of the participants 133(64.9%) believed that movement of teeth cannot occur without orthodontic appliances, 115(56.1%) believed that parents and guardians were responsible for the stability of the treatment results, while 88(42.9%) believed that dentists/orthodontists were responsible for the stability of the treatment outcomes. There were 132(64.4%) subjects who found removable retainer as a favourable retention device, while 71(34.6%) favoured fixed retainers. Conclusion: There was a notable gap in patients’ understanding of the retention phase, its importance and treatment durability expectations. Key Words: Orthodontic retainers, Retention, After treatment, Care goals, Awareness.